First Molecular Evidence of Theileria and Anaplasma Genospecies in Subulo gouazoubira Exhibiting Clinical Symptoms from Entre Ríos Province, Argentina - Sebastian, Patrick; Vaschalde, Paula Josefina; Pelosi, María Celeste; Flores, Fernando Sebastián; Yedro, Julio; Tarragona, Evelina Luisa (MDPI, 2025)
In November 2022, a male specimen of Subulo gouazoubira was found with signs of obnubilation and recumbency without the ability to maintain sternal or ambulatory posture. Based on the symptoms, serological, biochemical and molecular analyses were performed. The results of the biochemical blood analysis and the clinical signs were compatible with theileriosis. DNA of Theileria were detected in the blood sample by PCR analysis. The phylogenetic analysis of the obtained partial sequences of the 18S rDNA gen resulted in the identification of the detected strain as a Theileria genospecies closely related to Theileria spp. detected in other deer species. Further, a genospecies of Anaplasma was detected in the blood sample. This genospecies is located phylogenetically near to Anaplasma phagocytophilum. The results of this study demonstrate co-infection with two novel genospecies of Anaplasma and Theileria in a clinical case of a free-living S. gouazoubira for the first time in Argentina. However, the pathogenicity of these strains and specific role of S. gouazoubira in their enzootic transmission cycles remains unclear. To improve epidemiological understanding, assess risks and develop targeted control strategies, future studies should prioritize the isolation, characterization and cultivation of these genospecies and the assessment of vector competence.